Pemerolehan Kosakata Bahasa Korea Pada Pembelajar Dewasa Indonesia - Amanda Vira Maharani (Ranah: Jurnal Kajian Bahasa, 2019)
This study aims to find out the effects of Korean songs and videos on vocabulary size of adult Korean language learners through one-way communication. To collect the data, three respondents participated in a picture-naming task in Korean and questionnaire is used to know the frequency of the participants in listening to Korean songs and watching Korean videos. The result showed that acquiring vocabularies on adult learners is difficult because of motivation and age factors. All participants of this study have exposed to Korean content media for more than five years, yet none of them got a perfect score on vocabulary test, but they got different motivations for learning Korean. It can be concluded, the higher the motivation on learner is the better result the learner’s got. Korean vocabulary acquisition by listening to Korean songs and watching Korean videos is possible yet not easily acquired by adult learners. ABSTRAKPenelitian ini bertujuan untuk mengetahui pengaruh lagu dan video Korea pada kosakata pembelajar Bahasa Korea dewasa melalui komunikasi satu arah. Untuk mengumpulkan data, tiga responden berpartisipasi dalam penamaan gambar dalam Bahasa Korea dan kuesioner digunakan untuk mengetahui frekuensi peserta dalam mendengarkan lagu Korea dan menonton video Korea. Hasil penelitian menunjukkan bahwa memperoleh kosakata pada pelajar dewasa sulit karena motivasi dan faktor usia. Semua peserta penelitian ini telah terpapar ke media berkonten Korea selama lebih dari lima tahun, namun tidak satupun dari mereka mendapat nilai sempurna pada tes kosakata, tetapi mereka mendapat motivasi yang berbeda untuk belajar Bahasa Korea. Dapat disimpulkan bahwa semakin tinggi motivasi pada pelajar adalah hasil yang lebih baik pelajar dapatkan. Pemerolehan kosakata Bahasa Korea dengan mendengarkan lagu-lagu Korea dan menonton video Korea adalah mungkin namun tidak mudah diperoleh oleh pembelajar dewasa.